Bethe-Schwinger Effective Range Theory and Lehmann and Weinberg Chiral Perturbation Theories - Truong, Tran Nguyen (Communications in Physics, 2012)
This paper is a brief review of low energy soft hadronic physics,starting from the invention of the low energy effective rangetheory in the late 40’s due to Bethe and Schwinger fornucleon-nucleon scattering, and its generalization to the static Chew-Low model for pion nucleonscattering, to the present development of the Lehmann and WeinbergChiral Perturbation Theories. It is pointed out that a consistentlow energy calculation can be achieved with the incorporation ofthe unitarity relation in the Chiral Perturbation Theory